2017
DOI: 10.1155/2017/7357495
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase Inhibition Reduces Glucose Levels, Blood Pressure, and Oxidative Stress in Apolipoprotein E Knockout Mice

Abstract: Background Atherosclerosis is a multifactorial process. Emerging evidence highlights a role of the enzyme heparanase in various disease states, including atherosclerosis formation and progression. Objective The aim of the study was to investigate the effect of heparanase inhibition on blood pressure, blood glucose levels, and oxidative stress in apoE−/− mice. Methods Male apoE−/− mice were divided into two groups: one treated by the heparanase inhibitor PG545, administered intraperitoneally weekly for seven we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Under these conditions, the animals likely developed insulin resistance (T2D), which will augment hepatic VLDL output and decrease clearance via both HSPG-dependent and HSPG-independent mechanisms [6365]. Interestingly administration of the heparanase inhibitor, PG545, to chow-fed Apoe −/− mice reduced plasma glucose levels but had no significant impact on plasma triglyceride levels [70]. Whether PG545 impacts plasma triglyceride metabolism in animals fed a high-fat diet is unknown.…”
Section: Hepatic Heparan Sulfate Contributes To Trl Catabolismmentioning
confidence: 99%
“…Under these conditions, the animals likely developed insulin resistance (T2D), which will augment hepatic VLDL output and decrease clearance via both HSPG-dependent and HSPG-independent mechanisms [6365]. Interestingly administration of the heparanase inhibitor, PG545, to chow-fed Apoe −/− mice reduced plasma glucose levels but had no significant impact on plasma triglyceride levels [70]. Whether PG545 impacts plasma triglyceride metabolism in animals fed a high-fat diet is unknown.…”
Section: Hepatic Heparan Sulfate Contributes To Trl Catabolismmentioning
confidence: 99%
“…HPSE affects glucose metabolism in several disease settings, which could suggest a similar role in cancer. The inhibition of HPSE in the apolipoprotein-E-deficient mouse model of atherosclerosis resulted in a marked reduction of serum glucose levels [ 304 ]. In type-2 diabetes mellitus patients, urine HPSE was shown to correlate with high blood glucose levels, indicating glucose-mediated HPSE expression and secretion, with follow up in vitro studies showing insulin-mediated HPSE secretion by human embryonic kidney cells in culture [ 305 ].…”
Section: Introductionmentioning
confidence: 99%
“…During this study, it was first noted that, the PG545 treatment to both mock- and RRV-infected mice groups caused a reduction in weight gain across the treated groups. Other comparable murine studies of PG545 administration have also reported weight losses in treated animals [30].…”
Section: Discussionmentioning
confidence: 86%